The Routledge handbook of fiction and belief - James, Alison J.; Kubo, Akihiro; Lavocat, Françoise (Routledge, Taylor & Francis Group, 2024)
Cover -- Half Title -- Series Page -- Title Page -- Copyright Page -- Dedication -- Table of Contents -- List of Figures and Tables -- List of Contributors -- Introduction -- Part I: Believing in Fiction: Philosophical and Theoretical Perspectives -- 1 Belief, Imagination, and the Nature of Fiction -- 2 The "Willing Suspension of Disbelief": The Long History of a Short Phrase -- 3 The Fictionality of Games and the Ludic Nature of Fiction: Make-Believe, Immersion, Play -- 4 Fictional Emotions and Belief -- 5 Fictional Characters and Belief
Keywords: Soziale Einstellung; Politische Einstellung; Fiktion; Glaube; Literatur